Strengthening scientific literacy on nuclear reactor and its application through Nuclear School. (March 2019) - Taxwim,; Wahyono, P I; Biddinika, M K; Widodo, S; Aziz, M; Takahashi, F
Abstract: Amid its controversy for application in power generation, nuclear technology is still considered as promising technology for some other application such as in medicine, food, agriculture, water desalination, and other industrial uses. Therefore, knowledge on nuclear technology needs to be preserved and even to be improved. This paper presents an education and outreach activity on nuclear technology, called Nuclear School, as an effort to preserve and improve nuclear science and technology. It is held by the Center for Science and Accelerator Technology (PSTA), as a subsidiary of National Nuclear Energy Agency of Indonesia (BATAN). This activity allows physics and chemistry students, lecturers, and high school teachers in physics and chemistry engage with nuclear reactor and its scientists. By utilizing Kartini Reactor, a 100 kW(th) TRIGA Mark II research reactor type, the participants acquire basic nuclear science as well as reactor physics and operation both in classroom and practice. Safety aspect on radiation and nuclear reactor operation are also provided in order to improve public understanding on nuclear science and technology.